Infinite powers : How calculus reveals the secrets of the universe - Strogatz, Steven (Houghton Mifflin Harcourt, 2019)
Infinite Powers explains how calculus emerged and how its core ideas-limits, derivatives, and integrals-are used to understand change in nature and technology. The book shows how calculus underlies motion, growth, waves, disease patterns, and complex systems, and how it supports modern fields such as climate modeling, medicine, data analysis, and artificial intelligence.